Study of the excess Fe XXV line emission in the central degrees of the Galactic centre using XMM-Newton data - Anastasopoulou, Konstantina; Ponti, G.; Sormani, Mattia C.; Locatelli, N.; Haberl, F.; Morris, M. R.; Churazov, E. M.; Schödel, R.; Maitra, C.; Campana, S.; Teodoro, E. M. Di; Jin, C.; et al. (Astronomy and astrophysics, 2023)
The diffuse Fe XXV (6.7 keV) line emission observed in the Galactic ridge is widely accepted to be produced by a superposition of a large number of unresolved X-ray point sources. In the very central degrees of our Galaxy, however, the existence of an extremely hot (~7 keV) diffuse plasma is still under debate. In this work we measure the Fe XXV line emission using all available XMM-Newton observations of the Galactic centre (GC) and inner disc (−10° < ℓ < 10°, −2° < b < 2°). We use recent stellar mass distribution models to estimate the amount of X-ray emission originating from unresolved point sources, and find that within a region of ℓ = ±1° and b = ±0.25° the 6.7keV emission is 1.3-1.5 times in excess of what is expected from unresolved point sources. The excess emission is enhanced towards regions where known supernova remnants are located, suggesting that at least a part of this emission is due to genuine diffuse very hot plasma. If the entire excess is due to very hot plasma, an energy injection rate of at least ~6 × 10 40 erg s−1 is required, which cannot be provided by the measured supernova explosion rate or past Sgr A* activity alone. However, we find that almost the entire excess we observe can be explained by assuming GC stellar populations with iron abundances ~1.9 times higher than those in the bar/bulge, a value that can be reproduced by fitting diffuse X-ray spectra from the corresponding regions. Even in this case, a leftover X-ray excess is concentrated within ℓ = ±0.3° and b = ±0.15°, corresponding to a thermal energy of ~2 × 10 52 erg, which can be reproduced by the estimated supernova explosion rate in the GC. Finally we discuss a possible connection to the observed GC Fermi-LAT excess.
Gesehen am 27.11.2023